[Bus on Cliff of Snæfellsnes Peninsula] - Streng, Evelyn Fiedler (1975)
Photograph of a bus along the edge of a cliff on Snæfellsnes Peninsula. The light blue and white bus sits on the rocky side of a curving road carved into the side of a cliff. Green grass climbs up the upper half of the cliff to the right while a rocky drop into the large, blue ocean is visible to the left. A person in a long sleeved shirt and blue jeans walks alongside the bus to its left.